2016
DOI: 10.1111/obr.12396
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of internet‐delivered interventions providing personalized feedback for weight loss in overweight and obese adults

Abstract: SummaryBackgroundObesity levels continue to rise annually. Face‐to‐face weight loss consultations have previously identified mixed effectiveness and face high demand with limited resources. Therefore, alternative interventions, such as internet‐delivered interventions, warrant further investigation. The aim was to assess whether internet‐delivered weight loss interventions providing personalized feedback were more effective for weight loss in overweight and obese adults in comparison with control groups receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 47 publications
5
104
3
1
Order By: Relevance
“…. Reviews and meta‐analyses show that such mean weight losses of 5–6 kg are the most that are typically achieved via automated online programs developed by researchers and commercial providers .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…. Reviews and meta‐analyses show that such mean weight losses of 5–6 kg are the most that are typically achieved via automated online programs developed by researchers and commercial providers .…”
Section: Discussioncontrasting
confidence: 73%
“…Nevertheless, the average weight loss produced by WWO-E (over 5 kg) was similar to that observed in Steinberg et al (14). Reviews and meta-analyses show that such mean weight losses of 5-6 kg are the most that are typically achieved via automated online programs developed by researchers and commercial providers (2)(3)(4)(5).…”
Section: Obesity Science and Practicesupporting
confidence: 76%
“…For example, the Behavioral Intervention Technology model 7 builds on and integrates several other relevant models, [8][9][10][11] providing a framework for articulat-ing the relationship among the behavioral intervention 16 what features of computerized clinical decision support systems are effective, 17 and the importance of feedback in weight management DBCIs. 18 User engagement is also supported, undermined, or shaped by socio-contextual influences, such as the role played by family members and the broader cultural setting. Comprehensive models of engagement need to encompass not only individuallevel user dimensions but also the effects-positive and negative-of social dimen-sions.…”
Section: Conceptualizing Engagementmentioning
confidence: 99%
“…[30]). In the context of digital-based interventions for weight management, Hutchesson et al [39] point to the potential beneficial effects of self-monitoring and personalized feedback, and Sherrington and colleagues [40] found that internet-delivered weight loss interventions providing personalized feedback resulted in greater weight loss but only in the short term. …”
Section: The Active Ingredients Of Interventions: Behavior Change Tecmentioning
confidence: 99%
“…In the context of weight management in overweight/obese populations, previous reviews have reported positive albeit often small effects with considerable between-study variability [13,39,47]. There is therefore the need to identify which intervention components contribute to the effectiveness of digital-based interventions in promoting sustained weight management [13,39,40]. In a meta-analysis of internet-based interventions for health behavior change looking at the characteristics of most effective interventions, theory-based interventions incorporating a larger number of BCTs (vs. interventions with fewer BCTs) and using a variety of MoDs (e.g.…”
Section: Delivery Of Health Behavior Change Interventions: Digital Prmentioning
confidence: 99%